ENHANCING THE QUALITY OF HIGHER EDUCATION SERVICES IN UZBEKISTAN (Intent Research Scientific Journal, 2023)
Higher education plays a crucial role in shaping individuals' academic, professional, and personal development. As the demand for quality education continues to rise, ensuring the provision of high-quality higher education services has become paramount. This research article explores various strategies and implications for improving the quality of higher education services. It examines key factors influencing quality, explores innovative approaches to enhance teaching and learning, discusses the role of technology in quality improvement, and explores the significance of institutional support and governance. Additionally, this article addresses the importance of student engagement, faculty development, and quality assurance mechanisms in maintaining and enhancing the quality of higher education services. By shedding light on these critical aspects, this article aims to provide insights and recommendations for stakeholders involved in shaping the future of higher education.